The Effect of Work Motivation and Compensation on Employee Performance at Pos Bangunan in East Lombok - Muh. Mundzir Syakkar; Huzain Jailani; Susilawati Susilawati (Universitas Ibn Khladun Bogor, 2026)
This study aims to analyze the effect of work motivation and compensation on employee performance at Pos Bangunan in East Lombok, both partially and simultaneously. The background of this research is based on the phenomenon of declining company target achievement from 87% in 2024 to 80% in 2025, accompanied by indications of low work discipline and a suboptimal compensation system. This study employs a quantitative approach with a causal associative design. The research population consists of all 37 employees of Pos Bangunan, with sampling conducted using total sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 22. The results indicate that work motivation partially has a positive and significant effect on employee performance (t-count = 2.892; sig. = 0.007), while compensation partially has no significant effect on employee performance (t-count = 1.517; sig. = 0.138). Simultaneously, both variables together have a significant effect on employee performance (F-count = 21.676; sig. = 0.000) with a coefficient of determination of 56.0%. The resulting regression equation is Y = 10.517 + 0.627X₁ + 0.322X₂. These findings imply that strengthening work motivation should be prioritized in the human resource management strategy at Pos Bangunan, while compensation system improvements should not be neglected as a supporting factor.